From Allegory to Allegoresis (Itinera, 2015)
This paper aims to provide an excurcus on the presence and use of allegorical interpretation in Stoicism. In particular, Stoic philosophy represents a key moment for the evolution of the allegory in allegoresis, that is to say, as a systematic and rational interpretation of symbols and myths.